Guidelines in Clinical Practice: Examples of the Postpartum Period - Hilal Karadeniz; Hatice Yıldız (Dokuz Eylul University, 2021)
Clinical practice guidelines are systematically organized and scientifically developed summaries of the best evidence present. Thus, by transferring evidence-based practices to the clinical environment, it is possible to increase the patient safety and health care service quality. One of the most important factors that show the health care quality of a society is measured with the highest level of the maternal and infant health indicators of that society. However, the majority of preventable maternal and infant deaths, which are still undeniable, occur in the postpartum period. Therefore, the need to substantiate nursing care provided in the postpartum period on the best evidence is obvious. In this review article, it is aimed to give current literature information about the importance of clinical guidelines, the guideline development process and to examine the clinical practice guidelines published by the national and international organizations accepted as an authority in the field of women's health. With the information to be presented, it is aimed to increase the awareness regarding the development of guidelines and use in the clinical field in nursing care practices and to contribute to the health of mother and newborn.